A case with a ring chromosome 22 - Koç, Altuğ; Karaer, Kadri; Ergün, Mehmet Ali; Yirmibeş-Karaoğuz, Meral; Kan, Derya; Cansu, Ali; Perçin, Ferda (The Turkish Journal of Pediatrics, 2008)
Ring chromosome 22, a rare cytogenetic finding, was first described in 1968, and since then about 60 patients have been reported. We describe a new patient with ring chromosome 22 syndrome and discuss the common features of the previously reported cases. Our patient had the major features of this syndrome including mental retardation, hypotonia, motor delay, microcephaly, dysplastic large ears, lack of speech, and hyperactivity disorder. Magnetic resonance imaging findings also revealed an arachnoid cyst, found in the posterior cerebellum. In patients with ring chromosome 22, variable clinical manifestations may be seen due to the size of lost sequences near the telomere. By fluorescent in situ hybridization (FISH) technique, LSI DiGeorge/VCFS/ ARSA locus-specific probes are used to detect deleted sequences. We found that 22q11.2 regions were intact on both chromosomes 22, but 22q13.3 (Arylsulfatase A; ARSA region) was absent in the ring chromosome. As far as we know this is the first reported Turkish patient in the literature.